A case study on the usage of social network analysis to complement participant observation on Twitter (Simbiótica. Revista Eletrônica, 2021)
Based on digital ethnography conducted between 2013 and 2015 on the social network service Twitter, this article develops a theoretical-methodological discussion on the usage of data mining and network visualisation as a “quantitative” complement to the “qualitative” approach of participant observation. Starting from a literature review, this article argues that ethnography, from its beginnings, has been open to “quantitative” research. This article also tackles the anthropological origins of terminology and methodology regarding social network analysis, thus recovering the anthropological interest on the subject. Finally, based on an empirical case study, this article shows a possible usage of such methods as a way to enrich ethnographic analysis.Keywords: social anthropology; digital ethnography; network analysis; methodology. ResumenBasado en una etnografía digital conducida entre 2013 y 2015 en el servicio de red social Twitter, este artículo desenvuelve una discusión teórica-metodológica sobre el uso de la minería de datos y la visualización de redes como complemento “cuantitativo” al enfoque “cualitativo” de la observación participante. A partir de una revisión bibliográfica, sostiene que la etnografía, desde sus inicios, ha estado abierta a la investigación “cuantitativa”. Este artículo también aborda los orígenes antropológicos de la terminología y la metodología del análisis de redes sociales, recuperando así el interés antropológico por el tema. Por último, basándose en un estudio de caso empírico, demuestra un posible uso de dichos métodos como forma de enriquecer el análisis etnográfico.Palabras-clave: antropología social; etnografía digital; análisis de red; metodología. ResumoBaseado em etnografia digital conduzida entre 2013 e 2015 no serviço de rede social Twitter, este artigo desenvolve uma discussão teórico-metodológica sobre o uso de mineração de dados e visualização de redes como complemento “quantitativo” à abordagem “qualitativa” da observação participante. Partindo de uma revisão bibliográfica, argumenta que a etnografia, desde seus primórdios, esteve aberta a pesquisa “quantitativa”. Este artigo também aborda as origens antropológicas da terminologia e da metodologia de análise de redes sociais, recuperando, portanto, o interesse antropológico no tema. Por fim, baseado em um estudo de caso empírico, demonstra uma possível utilização de tais métodos como forma de enriquecer a análise etnográfica.Palavras-chave: antropologia social; etnografia digital; análise de redes; metodologia.